Inosine: A bioactive metabolite with multimodal actions in human diseases - Kim, In Soo; Jo, Eun-Kyoung (Frontiers in Pharmacology, 2022)
The nucleoside inosine is an essential metabolite for purine biosynthesis and degradation; it also acts as a bioactive molecule that regulates RNA editing, metabolic enzyme activity, and signaling pathways. As a result, inosine is emerging as a highly versatile bioactive compound and second messenger of signal transduction in cells with diverse functional abilities in different pathological states. Gut microbiota remodeling is closely associated with human disease pathogenesis and responses to dietary and medical supplementation. Recent studies have revealed a critical link between inosine and gut microbiota impacting anti-tumor, anti-inflammatory, and antimicrobial responses in a context-dependent manner. In this review, we summarize the latest progress in our understanding of the mechanistic function of inosine, to unravel its immunomodulatory actions in pathological settings such as cancer, infection, inflammation, and cardiovascular and neurological diseases. We also highlight the role of gut microbiota in connection with inosine metabolism in different pathophysiological conditions. A more thorough understanding of the mechanistic roles of inosine and how it regulates disease pathologies will pave the way for future development of therapeutic and preventive modalities for various human diseases.